Three-dimensional models of astrophysical magnetohydrodynamical jets - Murphy, Gareth Charles (Trinity College (Dublin, Ireland). School of Physics, 2007)
In the previous fifty years it has become clear that jets and outflows play a vital role in the formation of stars and com pact objects. Jets from young stellar objects typically show Herbig-Haro knots and bow shocks. Additionally, it now appears that (1) most stars form in binaries, and (2) jets from young stars are multiple and episodic outflows. Several groups have carried out large-scale simulations of jets, but often assuming a uniform ambient m edium and a single disk and star. In this thesis the problems associated with non-uniform media and binary systems are explored. In order to understand the role of jets in star formation the questions are asked; how do jets from binary stars behave? What is the effect of the prehistory of jets on their collimation, acceleration and morphology?
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin